Relationships between depressive symptoms and brain responses during emotional movie viewing emerge in adolescence - Gruskin, David C.; Rosenberg, Monica D.; Holmes, Avram J. (NeuroImage (Orlando, Fla.), 2020)
Affective disorders such as major depression are common but serious illnesses characterized by altered processing of emotional information. Although the frequency and severity of depressive symptoms increase dramatically over the course of childhood and adolescence, much of our understanding of their neurobiological bases comes from work characterizing adults’ responses to static emotional information. As a consequence, relationships between depressive brain phenotypes and naturalistic emotional processing, as well as the manner in which these associations emerge over the lifespan, remain poorly understood. Here, we apply static and dynamic inter-subject correlation analyses to examine how brain function is associated with clinical and non-clinical depressive symptom severity in 112 children and adolescents (7–21 years old) who viewed an emotionally evocative clip from the film Despicable Me during functional MRI. Our results reveal that adolescents with greater depressive symptom severity exhibit atypical fMRI responses during movie viewing, and that this effect is stronger during less emotional moments of the movie. Furthermore, adolescents with more similar item-level depressive symptom profiles showed more similar brain responses during movie viewing. In contrast, children’s depressive symptom severity and profiles were unrelated to their brain response typicality or similarity. Together, these results indicate a developmental change in the relationships between brain function and depressive symptoms from childhood through adolescence. Our findings suggest that depressive symptoms may shape how the brain responds to complex emotional information in a dynamic manner sensitive to both developmental stage and affective context. •Adolescents with worse depressive symptoms show less typical movie-driven brain activity.•Relationships between depressive symptoms and brain responses are stronger during less emotional moments of the movie.•Pairs of adolescents with more similar depressive symptom profiles share more similar brain responses to the movie.•Brain response typicality and pairwise similarity are unrelated to depressive symptoms in children.